The impact of endometrial mechanical stimulation in women with normal hysteroscopic findings undergoing IVF/ICSI: a meta-analysis - Li-Jun Lin; Jia Liu; Liang-Zhi Xu; Hui Chen (Clinical and Experimental Obstetrics & Gynecology)
Background: To investigate whether hysteroscopic endometrial mechanical stimulation improves pregnancy outcomes in patients undergoing in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI). Methods: We conducted a systematic search in electronic databases including PubMed, Embase, Cochrane Library, Web of Science from their inception to Feb 20th, 2021, as well as a manual search. All publications on the impact of hysteroscopic endometrial mechanical stimulation on IVF/ICSI outcomes were retrieved. Two reviewers independently screened the retrieved studies using stringent inclusion and exclusion criteria; data were subsequently extracted, and risk of bias was assessed. Meta-analysis of the selected studies was performed using Revman 5.3. Results: Eight studies involving 1494 patients were eligible for inclusion, including 5 randomized controlled trials and 3 prospective non-randomized simultaneous controlled experimental studies. We found that compared with the control group, hysteroscopic endometrial mechanical stimulation effectively increased live birth rate [risk ratio (RR) = 2.15, 95% confidence interval (CI) (1.78, 2.60), p < 0.00001] and clinical pregnancy rate [RR = 1.95, 95% CI (1.28, 2.98), p = 0.002], and also decreased abortion rate [RR = 0.54, 95% CI (0.35, 0.86), p = 0.009]. Subgroup analyses revealed that, hysteroscopic endometrial mechanical stimulation administered in the luteal phase in patients undergoing their first IVF/ICSI cycle was associated with significantly higher live birth rate and clinical pregnancy rate, as well as a significantly lower abortion rate. Discussion: Endometrial mechanical stimulation may improve live birth rate, clinical pregnancy rate and reduce abortion rate in patients with normal hysteroscopic findings who are undergoing IVF/ICSI. The benefits may be even greater if this therapy is given in the luteal phase and in patients who are in their first IVF/ICSI cycle. However, due to the limited quantity and quality of the included studies and variable stimulation methods, these findings should be interpreted with caution, and more high-quality studies are needed to confirm this conclusion.